Semantic Role with Promina Persona in Invitation Sentence An Analysis of Japanese and Indonesian Language - Kasmawati, Kasmawati (KIRYOKU, 2023)
In both Japanese and Indonesian, the semantic function linked with the invitation sentence contains markers from various word classes. The verb markers shiyou, shiyouka, and shinaika are used in inviting statements in Japanese. In Indonesian, invitation sentences are denoted by the adverbs mari and ayo. This is a qualitative descriptive study that employs note-taking techniques as well as the listening and AGIH method. According to the findings of this study, there are similarities in the semantic role that speakers have in the form of invitations shityou, shiyouka, and shinaika in Japanese while the adverb forms in Indonesia is mari and ayo, in which has a semantic role as main role of the actors. The last, the researcher invited the further researcher to conduct the similar study in exploring the syntactical features of inviting sentence in Japanese and other languages.